Dewan Komisaris Independen dan Komite Audit sebagai Faktor yang Menentukan Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Dewi, Aminar Sutra; Fernando, Ronal Trio (JURNAL PUNDI, 2020)
The purpose of this study is to discover the role of independent commissioners and audit committees to improve financial performance both simultaneously and in part. The paper objects used were all companies listed on the Indonesia Stock Exchange from 2013 to 2017, using a purposive sampling technique. Data on the company's annual financial statements and annual financial reports are obtained from the official website of the IDX. This paper was added in the study. The data analysis method used in this update is regression analysis in the data panel. This study uses the transition from Good Corporate Gorvernance, an independent board of commissioners and an audit board as an audit measure in this study. The results showed that the simultaneous independent board of commissioners had a significant effect on financial performance (ROA, ROE). The audit committee has a negative and not significant effect on financial performance (ROA, ROE).